Who goes home? Predictive factors in stroke recovery. Issue 1 (January 1985) - Henley, S; Pettit, S; Todd-Pokropek, A; Tupper, A
Abstract : One hundred and seventy two stroke patients were assessed two weeks post-stroke by a multi-disciplinary team. The predictive ability of a number of variables, including social, psychological and physical factors, was estimated for four outcome groups. Highly significant factors for good and bad outcome for one year were identified.